Psychological Barriers to the Use of Opioid Analgesics for Treating Pain in Patients With Advanced Recurrent Cancer: A Multicenter Cohort Study - Takehiko Tsuno; Takashi Kawaguchi; Ryota Yanaizumi; Junichi Kondo; Keiko Kojima; Takashi Igarashi; Masaki Inoue; Tomofumi Miura; Akime Miyasato; Kanako Azuma; Hiroshi Hamada; Tomoya Saeki; et al. (Palliative Medicine Reports)
Background: We aimed to gain insight into psychological barriers toward initiation of strong opioid analgesic use in patients with advanced recurrent cancer. Methods: This study included 46 patients who were prescribed with opioid analgesics for advanced recurrent cancer. The primary outcome was psychological barriers assessed using the Japanese version of the Barriers Questionnaire-II (JBQ-II). The secondary outcomes were psychological changes and pain relief one week after the induction of strong opioid analgesics. Results: The mean age of participants was 63.6 years. Furthermore, 26.1% had an Eastern Cooperative Oncology Group (ECOG) performance status of ≥3. The mean JBQ-II total score was 1.97 (95% confidence interval: 1.75–2.19). At the initiation of opioid therapy, there was no difference in the total scores between the baseline and one week later. Nevertheless, there was a significant difference in the subscale “disease progression” score (mean 2.97 vs. 2.59, difference in means 0.38, standard error 0.16, p = 0.026). Personalized Pain Goal (PPG) was achieved in about half of the participants, and a trend toward a higher score in the subscale “harmful effects” (concern about adverse events) was observed in those who did not achieve PPG. Conclusion: This study showed that patients with advanced recurrent cancer have psychological barriers to opioid induction. The relationship between the presence of psychological barriers before and after induction of opioid analgesics and the speed of pain improvement was determined. The results may provide fundamental information for prospective intervention studies to develop individualized education programs for patients with psychological barriers to opioids. Clinical Trial Registration Number UMIN000042443.